Monitoring and evaluating the social and psychological dimensions that contribute to privately protected area program effectiveness. (January 2019) - Selinske, Matthew J.; Howard, Natasha; Fitzsimons, James A.; Hardy, Mathew J.; Smillie, Kate; Forbes, James; Tymms, Karen; Knight, Andrew T.
Abstract: Privately protected areas (PPAs) make important contributions towards global conservation goals. As with any protected area, PPAs must be monitored for effectiveness at protecting and managing biodiversity. However, the key drivers of maintaining and improving the effectiveness of PPAs are often social, particularly for conservation covenants and easements that are owned and managed by private landholders. In Australia, we surveyed 527 covenant landholders across three states (New South Wales, Tasmania, and Victoria), to provide a benchmark for monitoring and evaluation activities. We found that landholders are mainly motivated to participate in order to protect their land in perpetuity, but come to expect financial and technical assistance as a benefit of the program. While 71.1% (n = 344) reported achieving their land management goals, 44.7% (n = 242) of landholders struggle with covenant management because of age, and financial and time constraints. Covenant landholders are generally satisfied with the program (92%). A subset (8%) of landholders feels disaffected with their participation, relating to their perceived inability to personally manage the biodiversity on their land, and the lack of interaction they have with representatives of covenanting organizations. Where compliance monitoring and semi-annual technical assistance is limited, some landholders are concerned that the efficacy of the covenant is reduced. To increase effectiveness we suggest that PPA programs regularly monitor landholder satisfaction and management needs, schedule conservation actions based on landholder capacity, and utilize landholder networks to spread information and foster communities of stewardship. Additionally, given the older demographics of landholders, programs should engage in PPA successional planning. Highlights: Monitoring and evaluating participant motivations, challenges and satisfaction is important for PPA effectiveness In Australia conservation values and protecting land in perpetuity are the main motivations to participate in PPA programs PPA landholders expect visits from stewardship officers for management guidance and enforcement monitoring PPA landholders face management challenges such as age, time, costs and lack of self-efficacy Social and psychological dynamism (management efficacy, satisfaction and ownership of covenants) present risks to PPAS